Case series on congenital malaria from a tertiary care hospital in North Eastern India - Das, Joydeep; Choudhury, Saugata (Asian Journal of Medical Sciences, 2021)
Malaria in early life is due to transfer of parasitized maternal red blood cell across placenta or direct transfer of parasite from placental syncytotrophoblast. Congenital malaria is defined as malaria acquired from mother in prenatal or perinatal period. Most of the cases in endemic area, passive transfer of high amount of maternal IgG antibody binds to malarial antigen and various components of parasites giving rise to various atypical clinical presentation. This case series will help neonatologist to think malaria in all non-specific symptoms of inconsolable cry, poor feeding, lethargy, even persistence of physiological jaundice. Very few reports of congenital malaria from India is reported in literature. Our series of five cases will address these few atypical symptoms.